Estudo das perdas de água no sistema de abastecimento e nas residências do conjunto Benjamim Sodré - VIÉGAS, Alessandro Abadessa (Universidade Federal do Pará, 2013)
This work presents a study of water losses in the water supply system of Benjamim Sodré Sector. The work was divided in two steps, as follows: experimental step and results step. Later, data were evaluated and the main results have focused on: characterization and evaluation of the consumers register, revenue and measured water from the down categories of the sector, as well as, the Water Supply System water flows. Besides that, it was made the calculation of some basic performance indicators, such as (index): water loss in the distribution (70,04%), water loss in the revenue (70,61%), water gross loss linear (157,96 L/m.d), connection water loss (1.446,41 L/connection.day), measurement (72,27%) and the global losses (70,93%). Also, it was possible to know the socioeconomic level of the population (30%) of the down categories R2 and R3 of the sector (176 houses), in which the results showed that about 94% of the interviewees who pay only the water bill affirmed to practice waster losses in their houses. The water quality was also analyzed. And it was verified that about 71,50% of the interviewees have considered it bad quality, which may contribute in a important way to the occurrences of Transmissible Hydric Diseases, because it was verified that 24% of the population presented problems concerning to diarrheas, worms, hepatitis A and scabies in the last years. It was made an evaluation of the water uses in the several domestic activities of the down categories R2 and R3. There is a loss of R$ 426,38 per month in the water bill of all consumers that contribute to water leaks in their homes. Finally, it is shown that for the activity of washing the dishes the consumer would have a reduction on the water bill average value of 89,28%. Additionally, to take bath: 43,66%, to wash clothes: 34,23%, to wash the sidewalk: 84,80%, and to brush their teeth 17,06%, referring the down categories R2 and R3.